What Open Access is not - López-López, Wilson (2015)
Recently, Redalyc shared the first edition of Peter Sauber’s book, which was first edited by the Massachusetts Institute of Technology and translated by Remedios Melero, of the Redalyc Scientific Committee. This book clears more than a few confusing aspects regarding what Open Access is and is not, which is very relevant for those who, like us, have chosen to use it for scientific communication. I will focus this editorial on what Open Access (OA) is not. Suber (2015) states the following: 1) It is not an attempt to avoid peer review; a part of our communities, especially in the human and social sciences, often equate OA with avoidance of peer-review and confound the common practice of not paying reviewers to review with lack of peer-review. Statements in OA publications certainly promote peer-reviewing processes. 2) OA does not try to change or refuse exploitation rights; open access uses works in the public domain with the consent of the holder of their rights. 3) OA is not an attempt to suppress the benefits from publication royalties; what it does is to point out that benefits from open access are probably higher than those of not earning royalties at all. 4) OA does not deny that there are associated costs, but it does suggest that alternatives to charging readers need to be found. 5) OA does not seek to end copyright; quite the contrary, it aims to acknowledge them. 6) OA is an attempt to end academic freedom; no, researchers are free to submit their products anywhere. 7) OA is not promoting plagiarism or disrupting anti-plagiarism; every OA policy promotes acknowledgment of authorship and in fact actions oriented towards the identification, regulation and punishment of plagiarism have led to the creation of entities such as COPE (Committee on Publication Ethics ) (López-López, 2014; Yong, Ledford, & Van Noorden, 2013). 8) OA is not an attack on traditional publishing houses; in fact, OA is a vehicle for promoting the work of researchers and institutions. 9) OA does not go against other editorial strategies or editors who do not share OA policies. 10) OA’s goal is not to force catering to non-academic audiences; open access seeks to facilitate a connection between researchers and the rest of academia, by trying to make knowledge available to anyone with Internet access. 11) OA does not imply universal access, since it cannot, by itself, control content filters put in place by entities and governments; it cannot avoid barriers imposed by language, disability or connectivity. I would also add a couple of additional misunderstandings. 12) OA does not promote the use of published output metrics such as citation analysis (SciELO), downloads and collaborations (Redalyc), or proprietary citation algorithms (Web of Science or Scopus). And finally, 13) OA does not promote the exclusion of publications from indexing systems. Suber’s book is very relevant, and needs to be consulted by editors, researchers and knowledge managers, since it clarifies the scope and limitations of open access. It is worth mentioning that this piece is a response to Jeffrey Beall’s unfortunate characterization of OA, SciELO and Redalyc as “favelas”, poorly grounded in reality. We share the views of many actors and entities who voiced their criticisms to those opinions. We believe that our systems have been a rigorous, viable, and sustainable alternative to inadequate practices centered in the commercialization of content. We have learned to live alongside private publishing houses, their metrics and regulations, but we agree that their model has certain flaws and that it does not represent the situation of scientific dissemination in Latin America and in other developing countries (Alperin et al., 2015).